PENINGKATAN HASIL BELAJAR BAHASA INDONESIA MELALUI METODE PROBLEM SOLVING SISWA KELAS IV SD NEGERI 1 SABARU PANGKEP - Salam, Abd Latif; Akbar, Fadly; Hanafiah (JURNAL SKRIPTA, 2024)
This research is Classroom Action Research conducted at Sabaru Pangkep State Elementary School which aims to improve students' Indonesian language learning outcomes through problem solving. This research was carried out in 2 cycles with each cycle consisting of four activity stages, namely the planning, implementation, observation and reflection stages. The variables in this research are improving learning outcomes as the dependent variable and the Problem Solving method which is the independent variable. The population in this study were Sabaru Pangkep State Elementary School students with a sample of 24 people, namely 10 female students and 14 male students with varying abilities. The data obtained was then analyzed using quantitative and qualitative analysis. Problem Solving has a positive impact in improving student learning outcomes, which is marked by an increase in the percentage of student learning completion. There was an increase in the completeness of Indonesian language learning outcomes by 25% from 70% in cycle I to 95% in cycle II. This shows that the Problem Solving learning method can improve Indonesian language learning outcomes.